1995
DOI: 10.1002/nau.1930140114
|View full text |Cite
|
Sign up to set email alerts
|

Location and concentration of estrogen, progesterone, and androgen receptors in the bladder and urethra of the rabbit

Abstract: The objective of this study was to determine location and concentration of estrogen, androgen, and progesterone receptors in the bladder and urethra of the rabbit. Two urethral and two bladder specimens were obtained from four 12-week-old female New Zealand white rabbits. Rat monoclonal antibody (AN1-15) to human androgen receptor and (H222) to human estrogen receptor and mouse monoclonal antibody (PR6) to chicken progesterone receptor were used. Immunocytochemical staining was performed and specimens were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 33 publications
3
50
1
1
Order By: Relevance
“…Consistent with prior reports in rodents [24,25], ERα was not detected in the nucleus or cytoplasm of the urothelium or stroma of the control bladders ( Figure 6A). Surprisingly, however, immunohistochemical analyses revealed nuclear ERα immunoreactivity in the basal urothelia of the urinary bladders of all groups treated with carcinogen with or without tamoxifen treatment (Fisher exact test, comparing to control, P < .05).…”
Section: Expression Of Ers In Bladder Tumors and Normal Urotheliumsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with prior reports in rodents [24,25], ERα was not detected in the nucleus or cytoplasm of the urothelium or stroma of the control bladders ( Figure 6A). Surprisingly, however, immunohistochemical analyses revealed nuclear ERα immunoreactivity in the basal urothelia of the urinary bladders of all groups treated with carcinogen with or without tamoxifen treatment (Fisher exact test, comparing to control, P < .05).…”
Section: Expression Of Ers In Bladder Tumors and Normal Urotheliumsupporting
confidence: 92%
“…Expression of ERβ in the normal urothelium has also been evaluated in several studies, and the preponderance of results indicates that this tissue is largely positive for ERβ [20][21][22][23] with the exception of one report that indicated that approximately one-third of the female specimens was ERβ-positive, while this receptor was undetected in 58 male samples [8]. In rodents, there appears to be negligible ERα nuclear staining in the bladder [24,25], but ERβ is expressed in the urothelium and smooth muscle in both sexes [26][27][28][29][30][31]. Thus, for both humans and rodents, ERβ appears to be the predominant ER expressed in normal urothelium.…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, androgen receptors were found in the highest concentrations in urethral and bladder epithelium, and the concentrations in smooth muscle were low or moderate (Rosenzweig et al, 1995). Androgen receptors were also identified on neurons in the medial preoptic area projecting to the pontine micturition center in male cats (Blok and Holstege, 1998).…”
Section: B Androgensmentioning
confidence: 99%
“…50 Androgen receptors have been found to be expressed in the epithelial cells of the urethra and the bladder of rabbits and in the urothelium, bladder smooth muscle, striated muscle cells of the proximal urethra and in the neurons in the autonomic ganglia of the prostatic plexus of the male rat. 51,52 The role of testosterone and its metabolites on maintaining the reflex activity in the pelvic part of the autonomic nervous system has been demonstrated in rats. 53 Upon castration, electrically evoked relaxations of the smooth muscle of the prostatic urethra were decreased and this effect was ascribed to an impaired ability of the smooth muscle to respond to relaxant agents.…”
Section: Sex Hormonesmentioning
confidence: 99%